1992
DOI: 10.1111/j.1365-2249.1992.tb05828.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 regulation of soluble IL-2 receptor levels following thermal injury

Abstract: SUMMARYIn theimmunosuppresscd burn patient serum levels of both IL-2 and a soluble form of IL-2 rcecptor alpha (.SIL-2R3;) are signilieantly elevated. Strikingly, the production of these markers hy the in vitro activated patients' cells is decreased. This study examines the role oriL-2 in the decreased production ol" Ihe sIL-2Ra in vitro in patients with major burns (n= 18. 30 to > 70% total body sulace area). Peripheral blood mononuclear cell (PBMC) cultures from patients with highly elevated serum sIL-2R2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Increased serum SIL-2R levels can cause immune escape, reduce interleukin-2 expression, and lead to a massive release of inflammatory factors, leading to systemic organ function syndrome and threatening the life safety of patients. [ 38 ] This study revealed that the serum SIL-2R levels in the SAP group are higher than that in the non-SAP group at admission, while the serum SIL-2R level in the death cases was higher than that in the surviving group patients. Moreover, Spearman correlation analysis shows that serum SIL-2R levels are positively correlated with APACHE II scores ( P < .001), suggesting that serum SIL-2R levels indicate SAP severity.…”
Section: Discussionmentioning
confidence: 85%
“…Increased serum SIL-2R levels can cause immune escape, reduce interleukin-2 expression, and lead to a massive release of inflammatory factors, leading to systemic organ function syndrome and threatening the life safety of patients. [ 38 ] This study revealed that the serum SIL-2R levels in the SAP group are higher than that in the non-SAP group at admission, while the serum SIL-2R level in the death cases was higher than that in the surviving group patients. Moreover, Spearman correlation analysis shows that serum SIL-2R levels are positively correlated with APACHE II scores ( P < .001), suggesting that serum SIL-2R levels indicate SAP severity.…”
Section: Discussionmentioning
confidence: 85%
“…sIL-2R is an immunosuppressive inhibitor of the synthesis and secretion of monocytes and activated T cells. It has a regulatory effect on the function of the interleukin-2 (IL-2)/IL-2R system and competes with IL-2R to bind IL-2, inhibit the IL-2 autocrine, and then reduce the IL-2 immune response (11,12). Related studies have confirmed that the upregulation of sIL-2R expression is accompanied by decreased B cell immune function (13).…”
Section: Discussionmentioning
confidence: 99%
“…Растворимые молекулы СD25 продуцируются активированными лимфоцитами. Сывороточный уровень sCD25 служит маркером их активации при различных патологических состояниях, в том числе при механической и ожоговой травме [2][3][4]. Взаимодействуя с интерлейкином 2, растворимые молекулы sCD25 по принципу обратной связи тормозят иммунные реакции, ограничивая чрезмерно развитый иммунный ответ при его гиперактивации.…”
Section: актуальные вопросы патофизиологии обоснованиеunclassified